O perdão como componente moral em crianças do primeiro ano do ensino fundamental - Lepre, Rita Melissa [UNESP]; Inácio, Amanda Kami Mura (My University, 2014)
Forgiveness may be considered a moral component to be developed along with the development of moral autonomy of individuals. This study aims to verify how 10 (ten) children from the first year of elementary school conceive the pardon and its possible relationship with their moral autonomy development. As theoretical research we have taken Piaget´s studies on human´s morality (1930; 1932) and Rique (2007, 2008, 2011) and Enright (1991, 1998) studies about forgiveness. This study was based on a qualitative research and the adopted method was the Piaget's Experimental Clinical Method. The results have shown that children perform moral reasoning when facing situations which involve the decision of forgiving someone and tend to comprehend forgiveness as forgiving someone for some performed act. We conclude by emphasizing the importance of the teacher’s mediation and intervention in moral discussions involving forgiveness, for the construction of the learners ´moral autonomy.

O perdão pode ser considerado um componente moral que deve ser desenvolvido em consonância à construção da autonomia moral dos sujeitos. Neste estudo buscamos verificar como 10 (dez) crianças do primeiro ano do ensino fundamental concebem o perdão e suas possíveis rela- ções com o desenvolvimento da autonomia moral. Como aporte teórico adotamos os estudos de Piaget (1930; 1932) sobre a moralidade humana e de Rique (2007, 2008, 2011) e Enrigth (1991, 1998) sobre o perdão. A pesquisa desenvolvida foi de caráter qualitativo e o método adotado foi baseado no clínio-piagetiano. Os resultados demonstraram que as crianças realizam raciocínios morais a partir de situações que envolvam a decisão de perdoar ou não e tendem a entender o perdão como desculpar alguém pelo ato cometido. Concluímos sublinhando a importância da mediação e intervenção do professor nas discussões morais que envolvam o perdão, visando a construção da autonomia moral dos educandos.
Forgiveness as a moral component in children of the first year of elementary school
Keywords: Autonomia moral; Desenvolvimento moral; Perdão; Moral autononomy; Moral development; Forgiveness